2002
DOI: 10.1016/s0969-2126(02)00748-7
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Mammalian 20S Proteasome at 2.75 Å Resolution

Abstract: The 20S proteasome is the catalytic portion of the 26S proteasome. Constitutively expressed mammalian 20S proteasomes have three active subunits, beta 1, beta 2, and beta 5, which are replaced in the immunoproteasome by interferon-gamma-inducible subunits beta 1i, beta 2i, and beta 5i, respectively. Here we determined the crystal structure of the bovine 20S proteasome at 2.75 A resolution. The structures of alpha 2, beta 1, beta 5, beta 6, and beta 7 subunits of the bovine enzyme were different from the yeast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
506
1
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 503 publications
(525 citation statements)
references
References 44 publications
13
506
1
5
Order By: Relevance
“…We here demonstrate that in addition, the third IFN-γ−inducible IP subunit β2i/MECL-1 contributes to reduced MART-1 epitope generation due to impaired N-and C-terminal cleavage site usage. Reduced N-terminal cleavage may be explained by the reduced β1-peptidylglutamyl peptide-hydrolyzing activity due to β1i/LMP2 (and a polar character of its substrate-binding pocket S1) incorporation into 20S proteasome complexes and for β2i/MECL-1 in that it also contributes to the formation of the S1 pocket of β1i/LMP2 [32,33]. Although concerted PA28α/β and IP-expression is increased following IFN-γ induction, PA28 can also be detected in tissues and cells with low IFN sensitivity such as muscle and erythrocytes that express SP complexes instead of IPs [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We here demonstrate that in addition, the third IFN-γ−inducible IP subunit β2i/MECL-1 contributes to reduced MART-1 epitope generation due to impaired N-and C-terminal cleavage site usage. Reduced N-terminal cleavage may be explained by the reduced β1-peptidylglutamyl peptide-hydrolyzing activity due to β1i/LMP2 (and a polar character of its substrate-binding pocket S1) incorporation into 20S proteasome complexes and for β2i/MECL-1 in that it also contributes to the formation of the S1 pocket of β1i/LMP2 [32,33]. Although concerted PA28α/β and IP-expression is increased following IFN-γ induction, PA28 can also be detected in tissues and cells with low IFN sensitivity such as muscle and erythrocytes that express SP complexes instead of IPs [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…These data show that ERAP1/2 negatively contributes to MART-1 26-35 epitope generation and that in particular, ERAP1 is responsible for the impairment of epitope presentation by IFN-γ. To study the underlying molecular mechanism, we next performed in vitro trimming experiments using recombinant ERAPs in combination with the N-terminally extended 14-mer epitope precursor peptide MART-1 [22][23][24][25][26][27][28][29][30][31][32][33][34][35] . As shown by reversed-phase HPLC analyses, ERAP1 efficiently trimmed the MART-1 22-35 precursor peptide.…”
Section: Erap1 Mediates Mart-1 26-35 Epitope Destructionmentioning
confidence: 99%
See 2 more Smart Citations
“…But this paper has the opposite result, and this is probably caused by the difference of structures of different species 20S proteasome. Unno et al has confirmed that the  subunits of human proteasome have some obvious structure differences with the  subunits of yeast proteasome, and the  subunits of human proteasome also have some structure differences with the  subunits of yeast proteasome (23).…”
Section: Discussionmentioning
confidence: 96%